1984
DOI: 10.1039/p29840002047
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic constants for tautomerism and ionization of pyridoxine and 3-hydroxypyridine in water–dioxane

Abstract: Thermodynamic values of the ionization constants and tautomeric equilibrium constants of pyridoxine and 3-hydroxypyridine were determined in dioxane-water at 25 "C. The Born model is unable to explain the effect of the solvent on these constants. The logarithms of the equilibrium constants calculated change linearly according to the logarithm of the molar water content in the mixture, up to 40% dioxane in the case of pyridine ionizations, and up to 70% dioxane (maximum content investigated) for the phenol ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 4 publications
3
30
0
Order By: Relevance
“…Studies on the solvent-dependent absorption spectra of pyridoxyl compounds have revealed that the existence of different tautomeric forms depends on the polarity of the solvent [24]. These tautomers are due to intramolecular H transfer from the protonated pyridinium HN group to the 3-O À -atom, a process that is favored in protic media [8].…”
mentioning
confidence: 98%
“…Studies on the solvent-dependent absorption spectra of pyridoxyl compounds have revealed that the existence of different tautomeric forms depends on the polarity of the solvent [24]. These tautomers are due to intramolecular H transfer from the protonated pyridinium HN group to the 3-O À -atom, a process that is favored in protic media [8].…”
mentioning
confidence: 98%
“…From the change of the absorption spectrum, the pK values of the different protonated forms of the ground state have been determined [3 ± 5]. Also, strong changes of the absorption characteristics of these compounds with the solvent polarity have been detected [6] [7]. These changes have been interpreted in terms of the different tautomeric forms present in the different media.…”
mentioning
confidence: 99%
“…Thus the above hypotheses (a) and (6) would explain the general behaviour of the thermodynamic magnitudes for the fust and second macroscopic protonation (Fi s. [1][2][3][4] and also E the differences between the values of AH, and -0As: for both protonations ( Figs. 1 and 2; Figs.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported in recent papers on the solution equilibria of compounds belonging to the vitamin B6 group and other analogous compounds in water-dioxane, with special emphasis on the ionization processes (1)(2)(3)(4)(5)(6). T o c a n y out these studies we designed an experimental method that allows us to calculate the macroscopic ionization equilibrium constants corrected to zero ionic strength, that is to say, the thermodynamic ionization equilibrium constants (1)(2)(3), with great saving in time and materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation